PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH (Studi Empiris pada Provinsi D.I Yogyaarta tahun 2008-2013) - Titi Yuli Astuti; Sunarto Sunarto (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study was to determine (1) the level of local financial independence in the province D.I. Yogyakarta (2) the influence of the local revenue of the level of local financial independence in the province D.I. Yogyakarta, and (3) the effect of general allocation funds to the level of financial independence in the region D.I. Yogyakarta province. This research is quantitative. The population in this study is D.I. Yogyakarta province of 2008-2013. The data used in this research is secondary data. Secondary data used was obtained APBD Realization Report of DPDPK city of Yogyakarta and BPS. The data have been collected and analyzed by the method of data analysis first conducted classical assumption test before hypothesis test. Testing the hypothesis in this study using multiple linear regression t test, F test, and test the coefficient of determination. The analysis showed local revenue positive and significant impact on the level of local financial independence with 15.661 t-test results with a significant level of 0.000, t-test bigger than ttable (15.661> 2.0639, general allocation funds do not affect the level of independence the financial area, with the t-count is smaller than t-table (-0.216